ChemInform Abstract: Iron(III) Chloride Catalyzed Synthesis of Highly Substituted Indolyl‐Tetrahydroquinoline Derivatives by Using Indolylnitroalkene as Dienophiles and Its Application to the Synthesis of Indolo‐Benzonaphthyridine Derivatives. Issue 19 (May 2015) - Zanwar, Manoj R.; Gawande, Sachin D.; Kavala, Veerababurao; Kuo, Chun‐Wei; Yao, Ching‐Fa
Abstract: An efficient iron(III) chloride catalyzed synthesis of highly substituted indolyltetrahydroquinoline derivatives from easily available starting materials, including indolylnitroalkenes, substituted anilines and various aldehydes is reported.